Analysis of the Accuracy of Diagnosis and Coding in Patient Medical Records at the Mutiara Delima Clinic Sawoo, Ponorogo Regency - Rismawati Rismawati; Ria Fajar Nurhastuti (program studi Rekam Medis dan Infomasi Kesehatan ITSK RS dr Soepraoen Malang, 2025)
This research aims to analyze the accuracy of diagnosis and coding in patient medical records at Mutiara Delima Sawoo Clinic, Ponorogo Regency, and to identify the factors influencing it. The research uses a descriptive method with a qualitative approach. Data were obtained through interviews with 1 medical records officer, observations with 1 medical records officer, 1 doctor, 3 midwives, 3 nurses, and the analysis of 260 medical record documents using instruments in the form of observation and interview sheets. The results show that out of the 260 patient medical records analyzed over one month, 31.54% were accurately coded with diagnosis and coding, 59.62% were diagnosed without coding, and 8.85% were neither diagnosed nor coded. The researchers recommend enhancing the training of medical personnel and strengthening the monitoring system to support service quality and insurance claims.